A low dicer expression is associated with resistance to 5‐FU‐based chemoradiotherapy and a shorter overall survival in patients with oral squamous cell carcinoma. (10th December 2013) - Kawahara, Kenta; Nakayama, Hideki; Nagata, Masashi; Yoshida, Ryoji; Hirosue, Akiyuki; Tanaka, Takuya; Nakagawa, Yoshihiro; Matsuoka, Yuichiro; Kojima, Taku; Takamune, Yasuo; Yoshitake, Yoshihiro; Hiraki, Akimitsu; et al.
<x xml:space="preserve">Abstract</x> Background The deregulation of microRNA (miRNA) is associated with multiple processes involved in cancer progression. RNase III endonucleases, Dicer and Drosha, are key enzymes for miRNA biogenesis, and it has been reported that altered expressions of these molecules affect the clinical outcomes of patients with various cancers. However, the clinical value of measuring the levels of Dicer and Drosha in oral squamous cell carcinoma (OSCC) patients is unclear. The purpose of this study was to determine the clinical significance of the expressions of Dicer and Drosha in patients with OSCC. Methods Oral squamous cell carcinoma specimens were obtained from 61 patients who underwent surgery following 5‐fluorouracil‐based chemoradiotherapy at Kumamoto University Hospital between October 2003 and January 2009. Paraffin‐embedded sections obtained from biopsy specimens were immunohistochemically analyzed. The associations between Dicer, Drosha, and various clinicopathological features were examined, and the effects of Dicer and Drosha on the prognosis were evaluated. Results A low Dicer tumor expression was significantly correlated with the pathological response to chemoradiotherapy. Furthermore, a Cox regression analysis based on the overall survival revealed the Dicer expression status (hazard ratio, 0.34; P = 0.048) and pathological response to chemoradiotherapy (hazard ratio, 0.21; P = 0.014) to be significant prognostic factors in OSCC patients. On the other hand, the Drosha expression was not associated with any clinicopathological features or the prognosis. Conclusion These results suggest that Dicer is a potential biomarker for predicting the clinical response to 5‐FU‐based chemoradiotherapy and the overall survival in patients with OSCC.